Assessment of Helicobacter pylori eradication rate of triple combination therapy containing levofloxacin - SEVEN, GÜLSEREN; Seven, GÜLSEREN; Cinar, Kubilay; Yakut, Mustafa; Idilman, Ramazan; Ozden, Ali (My University, 2011)
Background/aims: Owing to its high efficacy, ease of use, perfect adaptation and low complication profile, it is suggested that the triple therapy combination consisting of levofloxacin, amoxicillin and proton pump inhibitor may be an alternative for the first-line and second-line treatment of Helicobacter pylori. The aim of this study is to evaluate the efficacy of the triple therapy regimen containing two different doses of levofloxacin in the first-line eradication treatment. Material and Methods: 110 naive patients with anti Helicobacter pylori treatment indications according to Maastricht III Consensus Report were included to the study. Patients were randomized into two groups as the patients treated with a levofloxacin (500 mg o.i.d), amoxicillin (1 g b.i.d) and proton pump inhibitor (b.i.d) combination for 10 days (Group 1, n=60) and patients treated with a levofloxacin (500 mg b.i.d), amoxicillin (1 g bid) and proton pump inhibitor (b.i.d) combination for 10 days (Group 2, n=50). Eradication rate was assessed at the 6th week of therapy just subsequent to termination of treatment. Results: 110 treatment-naive patients (60 female, mean age: 44.1 +/- 14.7 years) were randomized and all patients completed the study. Helicobacter pylori eradication of the Group I was 60% and in Group 2 was 72.7%. The difference between the two groups was not statistically significant (p=0.427). None of patients experienced severe complication that would lead to discontinuation of therapy. Conclusion: It is observed that the efficacy of the triple therapy combination containing levofloxacin is not within acceptable limits for the first-line Helicobacter pylori eradication.